2018
DOI: 10.1177/1464884918791224
|View full text |Cite
|
Sign up to set email alerts
|

The cultural journalist around the globe: A comparative study of characteristics, role perceptions, and perceived influences

Abstract: This article presents a global-comparative study of journalists reporting about art and culture, that is, cultural journalists. In the literature, this particular group is said to be different from other types of journalists, because their professional work is guided more by an aesthetic logic than a news logic. Until now, however, this difference has mainly been studied in national contexts. Applying a global-comparative perspective by using data from The Worlds of Journalism Study, this article shows that cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 37 publications
0
35
0
4
Order By: Relevance
“…Others have argued that cultural journalists appear loyal towards artists and cultural producers, as they are often closely intertwined professionally or even personally, sharing the same passion for arts and culture (e.g., Forde, 2003;Kristensen, 2018). Hovden and Kristensen (2018) show that monitoring elites is less important to cultural journalists, who are more inclined to educate the audience, tell stories, and promote tolerance, i.e., to provide "a cultural filter" (Riegert et al, 2015;Roosvall & Widholm, 2018) on sociocultural issues. This is inconsistent with the adversary or watchdog role.…”
Section: Institutional Rolesmentioning
confidence: 99%
See 2 more Smart Citations
“…Others have argued that cultural journalists appear loyal towards artists and cultural producers, as they are often closely intertwined professionally or even personally, sharing the same passion for arts and culture (e.g., Forde, 2003;Kristensen, 2018). Hovden and Kristensen (2018) show that monitoring elites is less important to cultural journalists, who are more inclined to educate the audience, tell stories, and promote tolerance, i.e., to provide "a cultural filter" (Riegert et al, 2015;Roosvall & Widholm, 2018) on sociocultural issues. This is inconsistent with the adversary or watchdog role.…”
Section: Institutional Rolesmentioning
confidence: 99%
“…This suggests that cultural journalists adhere more to a subjective belief in how reality or truth can be conveyed, often basing their claims to truth on an analytical approach. For these reasons, cultural journalists have been labelled "journalists with a difference" (Forde, 2003;Hovden & Kristensen, 2018), who exercise "arts exceptionalism" (Harries & Wahl-Jorgensen, 2007) and apply an "aesthetic paradigm" (Hellman & Jaakkola, 2012).…”
Section: Epistemologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultural journalists are therefore often trained in arts and humanities rather than journalism. Empirical research has shown that cultural journalists perceive themselves as better educated than other journalists (e.g., Harries & Wahl-Jorgensen, 2007;Hovden & Knapskog, 2015), and they do, in fact, have more or a higher level of education than other types of journalists (Hovden & Kristensen, 2018). Th is has provided them with a mindset that focuses on aesthetic norms and values rather than news values, suggesting that cultural journalists tend to have one leg in academia and another in journalism (Kristensen & From, 2015b).…”
Section: Th Eory: Th E Specialised Practices Of Cultural Journalistsmentioning
confidence: 99%
“…Many cultural journalists work freelance and Nete Nørgaard Kristensen & Unni From Article: Cultural journalists on social media have loose media institutional couplings. Even today, a larger share of cultural journalists have non-permanent positions and work part-time compared to other types of journalists (Hovden & Knapskog, 2015;Hovden & Kristensen, 2018). Self-branding and proliferating the public self on social media may thus be particularly important to cultural journalists in this increasingly precarious job market.…”
Section: Th Eory: Th E Specialised Practices Of Cultural Journalistsmentioning
confidence: 99%